Comparative effectiveness among available treatments in difficult-to-treat port-wine stains (PWS): a Network Meta-Analysis of observational evidence - Sirinda Jamjanya; Voraphol Vejjabhinanta; Krittai Tanasombatkul; Phichayut Phinyo (Taylor & Francis Group, 2023)
Background Although pulsed dye laser (PDL) is the treatment of choice for port-wine stains (PWS), clinical resistance to PDL has been observed in 20-30% of cases. Several alternative treatment modalities have been introduced; however, there is still a lack of definite recommendations regarding the optimal treatment for difficult-to-treat PWS. Objective We aimed to systematically review and analyze the comparative effectiveness among treatments for problematic PWS. Methods & Materials We systematically searched for comparative studies assessing treatments for patients with difficult-to-treat PWS through relevant biomedical databases until August 2022. A Network Meta-Analysis (NMA) was conducted to estimate the odds ratio (OR) for all pairwise comparisons. The primary outcome is the improvement of lesions of more than 25%. Results Of the 2498 studies identified, six treatments from five studies were available for NMA. Compared with 585 nm short-pulsed dye laser (SPDL), intense pulsed light (IPL) was the most effective in clearing lesions (OR 11.81, 95% CI 2.15 to 64.89, very low confidence rating), followed by 585 nm long-pulsed dye laser (LPDL) (OR 9.95, 95% CI 1.75 to 56.62, very low confidence rating). The 1064 nm NdYAG, 532 nm NdYAG, and LPDL >585 nm exhibited potential superiority over SPDL 585 nm, although statistical significance was not observed. Conclusions IPL and 585 nm LPDL are likely to be more effective than 585 nm SPDL for treating difficult-to-treat PWS. Well-designed clinical trials are warranted to confirm our findings.